2008
DOI: 10.1682/jrrd.2008.01.0001
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study assessed feasibility and patient acceptance and estimated the magnitude of the clinical impact of physical telerehabilitation in patients with multiple sclerosis (MS). We recruited 12 consecutive patients with a known diagnosis of MS. Each patient received a custom-tailored rehabilitative exercise program prescribed by a physical therapist during a clinic visit. The patients were guided by the home telecare units in following their individualized exercise plan. After the patients used the physical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(8 citation statements)
references
References 56 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…With the feature of remote support of the patient, this app provides an opportunity of therapy extension between patient's home and clinic, allowing maintenance of contact with patients from wherever they are. Our results corroborate previous studies that reported high acceptance and satisfaction of blended therapy (defined as the combination of face-to-face therapy and remote support via TT) in patients with anterior cruciate ligament reconstruction, multiple sclerosis and hip/knee osteoarthritis ( 20 , 43 , 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…With the feature of remote support of the patient, this app provides an opportunity of therapy extension between patient's home and clinic, allowing maintenance of contact with patients from wherever they are. Our results corroborate previous studies that reported high acceptance and satisfaction of blended therapy (defined as the combination of face-to-face therapy and remote support via TT) in patients with anterior cruciate ligament reconstruction, multiple sclerosis and hip/knee osteoarthritis ( 20 , 43 , 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…[53][54][55] A vast array of digital technologies has been harnessed to support all aspects of MS care. 56 Examples include those which focus particularly on physical activity via web-based units of self-directed learning combined with exercise programmes prescribed by a physiotherapist and a texting or email service, 57 in-clinic prescribed exercise programmes combined with home-based automated prompt systems delivering reminders, 58 web-displayed physiotherapy-prescribed exercise routines alongside telephone calls or web-based asynchronous communication with physiotherapists. [59][60][61] None of these interventions however focus on people with high levels of disability and impairment and they do not combine real-time web conferencing to support patient-physiotherapist communication.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been carried out using TR as a treatment strategy for different clinical disorders, e.g., neurologic disease [stroke (43,44), spinal cord injury (45), multiple sclerosis (46,47)], cardiopulmonary disease (coronary artery, congestive heart failure) (48), musculoskeletal dysfunctions (49,50) and chronic pain and rheumatic diseases (51). For example, Finkelstein et al (52) in their pilot study in 12 patients with multiple sclerosis report that TR resulted in improvements in gait and balance at the 25-foot walk, 6min Walking Test (6mWT), and Berg Balance Scale (BBS). Another study by Marshall et al (53) showed TR to be effective in individuals with lung problems who did not have access to treatment.…”
Section: Introductionmentioning
confidence: 99%